UTILIZATION OF CORN AND ITS SUBSTANCES AS A SOURCE OF FISH FEED (ARTICLE REVIEW) - Prananda, Rizky; Andriani, Yuli (Jurnal Perikanan Unram, 2025)
Fish farming is highly dependent on the use of feed, which can even account for up to 70% of the total cost of farming. Therefore, the availability of quality feed in sufficient quantities is a key factor in ensuring successful farming. However, feed with high protein content tends to be expensive. The solution to this problem is to use alternative feed raw materials that have good nutritional content, do not compete with human needs, and are easy to obtain. Organic waste from corn harvest residues has great potential because it is easy to obtain and cheap. Corn waste has the problem of low nutritional content, so a fermentation process is needed as an effort to increase its nutritional value. This study aims to examine the extent to which the utilization of fermented corn waste can be used as fish feed to support increased fish growth performance.